2024
DOI: 10.1126/scitranslmed.adi0979
|View full text |Cite
|
Sign up to set email alerts
|

An orally bioavailable SARS-CoV-2 main protease inhibitor exhibits improved affinity and reduced sensitivity to mutations

Michael Westberg,
Yichi Su,
Xinzhi Zou
et al.

Abstract: Inhibitors of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) main protease (M pro ) such as nirmatrelvir (NTV) and ensitrelvir (ETV) have proven effective in reducing the severity of COVID-19, but the presence of resistance-conferring mutations in sequenced viral genomes raises concerns about future drug resistance. Second-generation oral drugs that retain function against these mutants are thus urgently needed. We hypothesized that the covalent hepatitis C virus prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…Thus, the authors , started from the structures of crystallized inhibitors, proposing new inhibitory peptidomimetics. Modifications of the known hepatitis C virus protease inhibitor boceprevir allowed obtaining orally bioavailable compounds, , and it was shown that they may be less sensitive to several mutations that cause resistance in the natural SARS-CoV-2 population . As the availability of computer modeling methods increases, researchers are gradually supplementing them with modern technologies of artificial intelligence and deep learning; ,, however, approaches based on screening of chemical libraries are also on top of their relevancy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the authors , started from the structures of crystallized inhibitors, proposing new inhibitory peptidomimetics. Modifications of the known hepatitis C virus protease inhibitor boceprevir allowed obtaining orally bioavailable compounds, , and it was shown that they may be less sensitive to several mutations that cause resistance in the natural SARS-CoV-2 population . As the availability of computer modeling methods increases, researchers are gradually supplementing them with modern technologies of artificial intelligence and deep learning; ,, however, approaches based on screening of chemical libraries are also on top of their relevancy.…”
Section: Introductionmentioning
confidence: 99%